2024
DOI: 10.1111/sms.14604
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial experiences of competitive rugby players on the “long, long journey” to recovery following ACL ruptures and reconstruction

Anel Borman,
Wayne Derman,
Heinrich Grobbelaar

Abstract: Anterior Cruciate Ligament (ACL) injuries are serious and potentially career‐ending. Reconstruction surgery and extended rehabilitation typically follow, but some athletes never attain the same level of sport performance. The psychosocial experiences of athletes who sustain ACL injuries and their cognitive appraisal, emotional and behavioral responses to the injury, and reconstruction require further attention during the different recovery phases. The aim is to explore these psychosocial experiences, social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have shown that ACL injuries are prevalent among young athletes engaged in sports involving frequent cutting, pivoting, jumping, or landing (Ithurburn et al, 2021). The psychological impact of ACL injuries on athletes is also noteworthy, with reports indicating that athletes prioritize physical and mental health, performance excellence, and career longevity during the recovery process (Borman, 2024). Additionally, the presence of symptoms of depression and anxiety following an ACL injury has been associated with poorer self-reported knee function, underscoring the importance of addressing the psychological aspects of recovery .…”
mentioning
confidence: 99%
“…Studies have shown that ACL injuries are prevalent among young athletes engaged in sports involving frequent cutting, pivoting, jumping, or landing (Ithurburn et al, 2021). The psychological impact of ACL injuries on athletes is also noteworthy, with reports indicating that athletes prioritize physical and mental health, performance excellence, and career longevity during the recovery process (Borman, 2024). Additionally, the presence of symptoms of depression and anxiety following an ACL injury has been associated with poorer self-reported knee function, underscoring the importance of addressing the psychological aspects of recovery .…”
mentioning
confidence: 99%